Excavations at Late Bronze Age tombs of Lori Berd - Devedjyan, Seda; Hobosyan, Suren (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
During the 2007-2008 field season seven tombs were excavated at Lori Berd. Four of these date to the end of the Late Bronze Age. One of the largest tombs (Tomb 81) of the site is located nearly in the centre of the cemetery, 70 m south of the Stepanavan-Lori Berd road. The oval (13.5 × 6.1 m) burial mound was composed of stones and soil, measured 0.6 m high. The centre was slightly sunken: it had a flat surface, and was oriented to the northwest – southeast. Sixteen large slabs forming the false vaulted roof of the burial chamber were discovered 0.2 – 0.4 m below the grass-covered mound. The four central stones were placed in the horizontal position, while the parameter stones were leaning towards the chamber.